Improving Students’ Vocabulary Through English Song - Mariana Mariana; Ahmad Laut Hasibuan; Risnawaty Risnawaty (Indonesian Journal of ELT and Applied Linguistics, 2021)
The article deals with improving students’ vocabulary through English song at SMK Einstein school . The research aims to improve the twelfth-grade students of SMK Einstein School in mastering vocabulary through English song. The research was conducted by Classroom Action Research (CAR). Techniques used to collect the data are planning, implementing, observing and reflecting. The researcher selected 30 students of class XII-SMK Einstein School academic year of 2020/2021. The instrument used in the research was the song lyrics.Songs can be trusted to help remember vocabulary and used the songs are interested in learning English. Memorizing song can be used to improve English vocabulary so that the purpose of learning English as a communication tool can be achieved optimally. It can be seen from the result of the research showed that there was improvement from Cycle I to Cycle II in the students’ participation in introduction, discussion and practice. In the students’ achievement Cycle I was 67,43, the average score of the Cycle II was 85. It can be concluded that songs have a significant impact on improving students’ vocabulary.